Magnetically Responsive Elastomer–Silicon Hybrid Surfaces for Fluid and Light Manipulation. Issue 2 (24th November 2017) - Yang, Zining; Park, Jun Kyu; Kim, Seok
Abstract: Stimuli‐responsive surfaces with tunable fluidic and optical properties utilizing switchable surface topography are of significant interest for both scientific and engineering research. This work presents a surface involving silicon scales on a magnetically responsive elastomer micropillar array, which enables fluid and light manipulation. To integrate microfabricated silicon scales with ferromagnetic elastomer micropillars, transfer printing‐based deterministic assembly is adopted. The functional properties of the surface are completely dictated by the scales with optimized lithographic patterns while the micropillar array is magnetically actuated with large‐range, instantaneous, and reversible deformation. Multiple functions, such as tunable wetting, droplet manipulation, tunable optical transmission, and structural coloration, are designed, characterized, and analyzed by incorporating a wide range of scales (e.g., bare silicon, black silicon, photonic crystal scales) in both in‐plane and out‐of‐plane configurations. Abstract : Responsive surfaces with an array of silicon scales sitting on ferromagnetic elastomer micropillars are constructed by transfer printing‐based deterministic assembly. Multiple functions, such as tunable wetting, droplet manipulation, tunable optical transmission and structural coloration, are realized by incorporating a wide range of scales (e.g., bare silicon, black silicon, photonic crystal scales) in both in‐plane and out‐of‐plane configurations.